2020
DOI: 10.3390/ijerph17103435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Resistance and Power Training on Cognitive Function in Older Women: A Randomized Controlled Trial

Abstract: The present study compared the effects of traditional resistance training (TRT) and combined power training (PT) and TRT (PTRT) on cognitive parameters and serum brain-derived neurotrophic factor (BDNF) levels in non-demented, well-functioning, community-dwelling older women. Forty-five older women were randomized into one of three experimental groups: TRT, PTRT, and control group (CG). Cognitive tests explored global cognitive function, short-term memory, and dual-task performance. Serum BDNF levels were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 89 publications
1
26
0
2
Order By: Relevance
“…That is, if muscle strength improves, then cognition improves and vice versa. A recent study reported that different muscle strength and power training programmes improved cognitive functioning globally in the active groups with respect to the control group (inactive) [50].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…That is, if muscle strength improves, then cognition improves and vice versa. A recent study reported that different muscle strength and power training programmes improved cognitive functioning globally in the active groups with respect to the control group (inactive) [50].…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have shown the effectiveness of muscle strength and power training [44][45][46][47]; however, precaution is also recommended in the evaluation of this population regarding the adaptation to the loads [48]. Similarly, many studies have reported improvements in the cognition level in people who carried out muscle strength training programmes [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with those of other studies, which report that different strength training programmes (resistance training) improve cognitive function. It seems to be clearly demonstrated that controlled and planned physical exercise improves cognitive impairment, besides physical and psychosocial health in older adults [ 1 , 14 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors agree on the need for further longitudinal studies to determine with more precision the independent effect of different sedentary behaviours on cognitive functions [ 67 , 68 , 69 ], and to establish the most efficient type of exercise and characteristics of training programmes to counteract cognitive impairment [ 59 , 64 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, lifestyle modifications have been recognized by the scientific community as possible tools to counteract age-related cognitive decline. Physical activity and exercise, for example, have been extensively examined and investigations have indicated that older adults engaged in exercise programs might benefit from improvements in cognition, 10 - 12 although these findings were not unanimous. 13 Diet patterns have also been subject to investigation.…”
Section: Introductionmentioning
confidence: 99%